2016
DOI: 10.18632/oncotarget.12675
|View full text |Cite
|
Sign up to set email alerts
|

CD133+CD54+CD44+ circulating tumor cells as a biomarker of treatment selection and liver metastasis in patients with colorectal cancer

Abstract: IntroductionLiver is the most common site of distant metastasis in colorectal cancer (CRC). Early diagnosis and appropriate treatment selection decides overall prognosis of patients. However, current diagnostic measures were basically imaging but not functional. Circulating tumor cells (CTCs) known as hold the key to understand the biology of metastatic mechanism provide a novel and auxiliary diagnostic strategy for CRC with liver metastasis (CRC-LM).ResultsThe expression of CD133+ and CD133+CD54+CD44+ cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…It was further showed that CD133 + CD44 + CD54 + subpopulation of CTCs was an independent prognostic factor for CRC patients with liver metastasis (HR = 6.459; 95% CI = 1.461–28.558; P = 0.014). In our previous research, we had reported that CD133 + CD44 + CD54 + subpopulation of CTCs in the peripheral blood was associated with liver metastasis and could be used as an auxiliary diagnostic marker for liver metastasis among CRC patients . This is the first study that reports CD133 + CD44 + CD54 + subpopulation of CTCs has a prognostic value in CRC patients with liver metastases, especially those who did not receive surgical treatment for metastases ( P < 0.001).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…It was further showed that CD133 + CD44 + CD54 + subpopulation of CTCs was an independent prognostic factor for CRC patients with liver metastasis (HR = 6.459; 95% CI = 1.461–28.558; P = 0.014). In our previous research, we had reported that CD133 + CD44 + CD54 + subpopulation of CTCs in the peripheral blood was associated with liver metastasis and could be used as an auxiliary diagnostic marker for liver metastasis among CRC patients . This is the first study that reports CD133 + CD44 + CD54 + subpopulation of CTCs has a prognostic value in CRC patients with liver metastases, especially those who did not receive surgical treatment for metastases ( P < 0.001).…”
Section: Discussionmentioning
confidence: 85%
“…Peripheral blood samples were obtained from CRC patients attending our department and an informed consent was obtained from all the individuals. Peripheral blood samples were collected and prepared as per the protocol described in our previous report . In detail, CTCs from cell suspensions were characterized by multiparameter flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, eTumorType is capable of discriminating cancer types, which is beyond the current studies on CTC or cfDNA data, as the majority of these studies only focused on finding features ( e.g. , CNV, mutation, microRNA, methylation, and gene expression) associated with specific cancer types [25], [26], [27], [28], [29], [30]. To our best knowledge, no such algorithms have been developed so far.…”
Section: Discussionmentioning
confidence: 99%